2000
DOI: 10.1136/bmj.320.7241.1053
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of nurse telephone consultation in out of hours primary care: evidence from a randomised controlled trial

Abstract: Objective To undertake an economic evaluation of nurse telephone consultation using decision support software in comparison with usual general practice care provided by a general practice cooperative. Design Cost analysis from an NHS perspective using stochastic data from a randomised controlled trial. Setting General practice cooperative with 55 general practitioners serving 97 000 registered patients in Wiltshire, England. Subjects All patients contacting the service, or about whom the service was contacted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 9 publications
2
81
0
4
Order By: Relevance
“…While some empirical studies in the clinical literature have shown that nurse lines may generate savings (Lattimer et al 2000), there…”
Section: Discussionmentioning
confidence: 99%
“…While some empirical studies in the clinical literature have shown that nurse lines may generate savings (Lattimer et al 2000), there…”
Section: Discussionmentioning
confidence: 99%
“…34 Odyssey PatientAssess has been evaluated in a number of other RCTs, and its clinical effectiveness and cost-effectiveness in settings other than in-hours general practice is already established. For instance, it has been demonstrated to be safe and cost saving in the long term in one study 5,16 involving a co-investigator compared with GP telephone triage in a trial of out-of-hours primary care consultations. That study remains the largest trial of nurse telephone triage to date.…”
Section: Computer Decision Support In Nurse Triagementioning
confidence: 99%
“…That study remains the largest trial of nurse telephone triage to date. 5,16 Furthermore, in excess of 60% of PCTs currently commission out-of-hours primary care services that use nurses to triage patients by telephone, supported by Odyssey PatientAssess (Chris Coyne, Plain Healthcare, 2008, personal communication). However, the findings and experience of out-of-hours primary care (providing care for around 10.8 million contacts per year in UK) cannot necessarily be generalised to the very different system providing in-hours primary care and experiencing around 1 million contacts per working day.…”
Section: Computer Decision Support In Nurse Triagementioning
confidence: 99%
“…These applications also substantially decreased emergency department visits and hospitalizations, prolonged survival, and led to impressive cost savings [23,24].…”
Section: Discussionmentioning
confidence: 98%